Pakistan Army Green Book 2006 : Terrorism - Pakistan Army; Editorial Board : Mushtaq Bhatti, Muhammad Brig.; Taimur Sabir Bhatti Lt. Col. and Naseer Ahmad Satti Lt. Col. (GHQ, Rawalpindi, Pakistan Pakistan Army, 2008)
Content of the book are the writers' personal views and are not be taken as official opinion/policy
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals